Study of Thai Language Oral Reading Problems for Students with Down Syndrome: Grade Range 1 - Kaewchote, Nantawan; Chongchaikit, Maturos (Journal of the American Academy of Special Education Professionals, 2011)
The purpose of the study was to explore the Thai Language Oral Reading Problems of students with Down syndrome, Grade Range1 at Watnonsaparam School, Saraburi Thailand in favor of Web Quest Lessons Development Enhancing Oral Reading Skills of Down syndrome Students. The research instruments were the 2 observation forms on Thai Language Reading skill. The findings revealed that Thai Language Oral Reading Problems of Down syndrome students varied greatly on the pronunciation of vowels, tone marks, wording and sentences. Nevertheless, four students were able to orally read Thai characters with correct pronunciation and showed basic understanding of reading procedures. Most of the students were having problems in reading Thai vowels both in terms of pronunciation and meaning decoding; they took much more time on reading procedures. The problems found will benefit the development of Web Quest Lessons Enhancing Oral Reading Skills of Down syndrome Students Grade Range 1 at Watnonsaparam School, Saraburi Thailand.